Pengaruh Stakeholder Terhadap Carbon Emission Disclosure - Desy Nur Pratiwi (Accounthink, 2017)
This study aims to obtain empirical evidence of the influence of stakeholders on the carbon emission disclosure. Measurement of carbon emission disclosure is based on the carbon disclosure project. The population in this study is the manufacturing and mining company listed on the Indonesia Stock Exchange (BEI) in the period 2013 – 2015. The sampling technique used in this research is purposive sampling method with sample number 85. The data analysis technique used is multiple linear regression. The test results showed that the positive effect on the regulation of carbon emission disclosure, institutional ownership positively affects carbon emission disclosure. However, leverage has no effect on carbon emission disclosure.